1998
DOI: 10.1034/j.1399-3054.1998.1020106.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of peanut with a soybean vspB promoter‐uidA chimeric gene. I. Optimization of a transformation system and analysis of GUS expression in primary transgenic tissues and plants

Abstract: Direct DNA delivery via microprojectile bombardment has become an established approach for gene transfer into peanut (Arachis hypogaea L.). To optimize our transformation protocol and to simultaneously explore the function of a heterologous promoter whose activity is developmentally regulated, embryogenic cultures from three peanut cultivars were bombarded with two plasmid constructs containing a uidA gene controlled by either a soybean vegetative storage protein gene promoter or a cauliflower mosaic virus 35S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Similar results were previously shown by Yang et al (1998), who reported that 92% of cell lines PCR-positive for the hygromycin resistance gene also showed PCR amplification of the nucleocapsid protein gene of tomato spotted wilt virus, and Wang et al (1998) who reported that 92% of hygromycin-resistant and PCR-positive cell lines showed PCR amplification of the vspB promoter-driven reporter gene, b-glucuronidase. It is likely that the non-selected gene linked with hph was disrupted in some instances during plasmid DNA integration.…”
Section: Presence and Integration Of The Cpo-p Gene In Peanutsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were previously shown by Yang et al (1998), who reported that 92% of cell lines PCR-positive for the hygromycin resistance gene also showed PCR amplification of the nucleocapsid protein gene of tomato spotted wilt virus, and Wang et al (1998) who reported that 92% of hygromycin-resistant and PCR-positive cell lines showed PCR amplification of the vspB promoter-driven reporter gene, b-glucuronidase. It is likely that the non-selected gene linked with hph was disrupted in some instances during plasmid DNA integration.…”
Section: Presence and Integration Of The Cpo-p Gene In Peanutsupporting
confidence: 76%
“…Tissues that were actively growing on liquid selection medium were transferred to agar medium containing 20 mg/mL hygromycin, and individual pieces were assigned a unique cell line number. Thirteen bombardment experiments with 107 plates yielded 147 hygromycin-resistant cell lines for an average of 1.37 cell lines per plate, which is within the reported peanut transformation efficiency range of 0.8 to 4.6 hygromycin resistant callus lines per bombardment (Higgins et al 2004;Ozias-Akins et al 1993;Wang et al 1998;Yang et al 1998). It is difficult to get accurate transformation efficiency data based on somatic embryo numbers bombarded since clusters of somatic embryos contain variable numbers, and some cell lines may have originated from the same transformation event but were separated due to agitation during liquid selection.…”
Section: Selection and Regeneration Of Transformed Callusmentioning
confidence: 68%
“…Plasmid DNA was isolated from recombinant E. Coli by the alkaline lysis method and was purified with 13% PEG solution [8]. Particles coated with plasmid [1] were bombarded into cotyledons using a PDS 1000/helium-driven apparatus (Bio-Rad, CA, USA). Each bombardment delivered approximately 1 μg DNA and 300 μg gold particle 1.0 mm in diameter.…”
Section: Plasmid Constructs and Microprojectile Bombardmentmentioning
confidence: 99%
“…Genetic engineering provides a prospective way to reduce certain problems by transferring individual genes for pest resistance or other traits into elite germplasm of a cultivated species. Transgenic peanut plants have been produced by particle bombardment [1] and via Agrobacterium-mediated transformation [2]. Microprojectile bombardment uses high velocity particles to penetrate cell walls and to deliver DNA into intact plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic peanut plants have been produced by particle bombardment [4] and via Agrobacterium-mediated transformation [5]. Microprojectile bombardment uses high velocity particles to penetrate cell walls and to deliver DNA into intact plant cells.…”
Section: Introductionmentioning
confidence: 99%